Healthfulness of Fast-Food and Full-Service Restaurants in 16 Georgia Counties after Mandatory Menu Labeling - Janani Rajbhandari-Thapa; Donglan Zhang; Nicole Katapodis; Dana Alvin; Melanie Andrews (Georgia Southern University, 2022)
Background: Despite that the effect of menu labeling on consumer choices has been studied, there are gaps in the research on the healthfulness of the restaurant food environment post-mandatory menu labeling, specifically in the Southern United States. This study aims to assess the healthfulness of fast-food and full-service chain restaurant environments after compliance with mandatory menu labeling. Methods: The healthfulness of 46 representative fast-food and full-service chain restaurants in 16 Georgia counties was examined using the Nutritional Environment Measures in Restaurants (NEMS-R) survey. The scores were compared between full-service and fast-food restaurants using t-tests across several healthfulness measures such as facilitators and barriers to healthful eating. Results: Fast-food restaurants had more barriers to healthy eating than full-service restaurants. Specifically, fast-food restaurants, compared to full-service restaurants were more likely to encourage large portions (60.9% vs. 17.4%, p=0.006) and offer combination meals at a cheaper price than the sum price of individual items (56.5% vs. 21.7%, p=0.033). Conclusions: Findings on the post-menu labeling chain restaurant food environment in our study does not show improvements from the extant evidence on pre menu labeling food environment. Further, NEMS-R scores for both fast-food and full-service restaurants indicated the need for improvements in the healthfulness of chain fast-food and full-service restaurants' food environments.